2014
DOI: 10.4070/kcj.2014.44.6.400
|View full text |Cite
|
Sign up to set email alerts
|

Slow Coronary Flow Phenomenon and Increased Platelet Volume Indices

Abstract: Background and ObjectivesWe sought to determine the relationship between mean platelet volume (MPV), platelet distribution width (PDW), and platelet larger cell ratio (P-LCR) with slow coronary flow (SCF).Subjects and MethodsEighty participants who underwent coronary angiography were divided into two groups, 50 participants with SCF as case group, and 30 with normal coronary flow (NCF) as control group. Baseline characteristics and laboratory data were collected before angiography.ResultsPlatelet volume indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
3
10
1
1
Order By: Relevance
“…These findings are in agreement with Signori et al 11 who found that BMI was higher in CSF patients than in control groups with p < 0.044 and also, Gunes et al found that BMI was higher in CSF patients compared to control group, although it was within normal limits also 15 . However, Mir Hossein et al found that there were no significant differences between CSF and control group 16 . Our finding can be explained by that the CSF patients tend to have more metabolic syndrome than controls, a finding that may be associated with increased peripheral resistance.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in agreement with Signori et al 11 who found that BMI was higher in CSF patients than in control groups with p < 0.044 and also, Gunes et al found that BMI was higher in CSF patients compared to control group, although it was within normal limits also 15 . However, Mir Hossein et al found that there were no significant differences between CSF and control group 16 . Our finding can be explained by that the CSF patients tend to have more metabolic syndrome than controls, a finding that may be associated with increased peripheral resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Several reports have demonstrated that the mean platelet volume is higher in patients with CSFP compared to individuals with normal coronary arteries;10–12 however, in one study the elevated mean platelet volume has not been associated with CSFP 13. Other platelet volume indices, including platelet distribution width and platelet–large cell ratio, have been associated with the presence of CSFP 6. On the other hand, the relationship between leukocyte subtypes and the CSFP has been inconsistent in previous studies.…”
mentioning
confidence: 81%
“…On the other hand, the relationship between leukocyte subtypes and the CSFP has been inconsistent in previous studies. In most of the studies, total white blood cell count has not been the predictor of CSFP 6,1315. In contrast, Akboga et al16 found that a higher white blood cell count is associated with CSFP.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[10] Increased platelet activation plays an active role in the development of inflammation. [11][12][13][14][15][16][17][18] It was found that platelets significantly contribute to the inflammatory process, such that platelet indices, including mean platelet volume (MPV), platelet distribution width (PDW), and platelet count (PC), may be used as an index for inflammatory conditions caused by autoimmune conditions or infection. [11][12][13][14][15][16][17][18] Sometimes, it may be difficult to diagnose patients with DNSI early during the course of acute tonsillitis.…”
mentioning
confidence: 99%